Effect of Zeba (Super absorbent polymer) to combat the impacts of increased temperature and irrigation interval on growth and yield attributes of Chilli (Capsicum annum) - Rasanjali, K.G.A.I.; De Silva, C.S; Jayakody, L.K.R.R. (Universitas Andalas, 2023)
It is very important to use adaptation technologies in crop fields to mitigate the adverse effect of increasing temperature and limited amount of water on crop growth and yield. Application of Super Absorbent Polymers is one of the technologies which can be used to overcome the impacts. This study was conducted at the Open University of Sri Lanka, during the period of 2019 to 2021. Experimental design consisted with three factors, i.e. temperature conditions (32-33 0C and 35-360C), irrigation intervals (3days, 5days and 8days) and application of Zeba (Super Absorbent Polymers) (2g of Zeba and with not Zeba). Treatments were arranged in Complete Randomized Design with three replicates. Growth and yield parameters of chilli were collected and statistical analysis of the data (ANOVA) was performed using Three-Factor Factorial Design and compared for the significance by using a Revised Least Significant DifferenceÂ test at p=0.05. According to the results, Zeba positively influences to mitigate the adverse effect of increased temperature and water stress condition imposed by longer irrigation interval. Under ambient temperature condition, treatment with Zeba, three day irrigation interval showed the highest yield of chilli. However, the yield of that crop was not significantly different from the treatments with five day irrigation interval and eight day irrigation interval under ambient temperature condition with Zeba. Therefore, due to the no significant difference, treatment with Zeba and eight day irrigation interval can be named as the best cost-effective treatment which can be used to cultivate with limited amount of water under ambient temperature condition. Under increased temperature condition, treatment with Zeba, three day irrigation interval showed the highest yield. However, it is not significantly different from the treatment of five day irrigation interval, with Zeba under increased temperature condition. Therefore, under increased temperature condition, irrigation interval can be extended up to five day when plants were treated with Zeba.